Sample Preparation-Quo Vadis Current Status of Sample Preparation Approaches-2nd Edition - Samanidou, Victoria; Panderi, Irene (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Sample preparation is and will always be the most important step in chemical analysis. Numerous techniques, methods, methodologies, and approaches are published in the literature offering a wide range of analytical tools to the lab practitioner. Analytical scientists all over the world are trying to develop protocols for a plethora of analytes in various sample matrices. In the last decade, sample pre-treatment advances have followed green chemistry and green analytical chemistry demands, focusing on miniaturization and automation, using the least possible amount of organic solvents. The question is how far we have been till now, and what the future perspectives are. To answer this question, analytical chemists were invited to share their experience in the field and report on the recent advances in sample-preparation approaches. The outcome of our invitation was eleven excellent manuscripts, including four review articles and seven original research articles in the first edition of the Special Issue "Sample Preparation-Quo Vadis: Current Status of Sample Preparation Approaches".The second edition is a collection of ten significant contributions to the field of sample preparation. It includes two highly interesting and comprehensive review articles and eight innovative research articles.